Do School Budgets Matter? The Effect of Budget Referenda on Student Performance - Kyung-Gon Lee; Solomon Polachek (Institute for the Study of Labor (IZA), 2014)
This paper analyzes how changes in school expenditures affect dropout rates and standardized test scores based on data from 465 school districts in New York during the 2003/04 to the 2008/09 school years. Past traditional regression approaches show inconsistent results of school expenditures because of an endogeneity problem. The regression discontinuity design used in this study isolates exogenous variation in school expenditures per pupil by comparing school districts where budget referenda passed and failed by narrow margins. The results indicate that increases in school expenditures reduce dropout rates but have limited effects on student test scores.
Keywords: I20; I21; I22; 330; educational expenditures; school budget referenda; school dropout rates; student performance